The abortion trend after the pronatalist turn of population policies in Iran: a systematic review from 2005 to 2022 - Shirdel, Elham; Asadisarvestani, Khadijeh; Kargar, Fatemeh Hami (BMC public health, 2024)
OBJECTIVE: Given Iran's recent shift towards pronatalist population policies, concerns have arisen regarding the potential increase in abortion rates. This review study examines the trends of (medical), intentional (illegal), and spontaneous abortions in Iran over the past two decades, as well as the factors that have contributed to these trends. METHODS: This paper reviewed research articles published between 2005 and 2022 on abortion in Iran. The study employed the PRISMA checklist for systematic reviews. Articles were searched from international (Google Scholar, PubMed, Science Direct, and Web of Science) and national databases (Magiran, Medlib, SID). Once the eligibility criteria were applied, 42 records were included from the initial 349 records. RESULTS: Abortion is influenced by a variety of socioeconomic and cultural factors and the availability of family planning services. Factors that contribute to unintended pregnancy include attitudes toward abortion, knowledge about reproductive health, access to reproductive health services, and fertility desires, among others. In addition to health and medical factors, consanguineous marriage plays an important role in spontaneous and therapeutic abortion. A higher number of illegal abortions were reported by women from more privileged socioeconomic classes. In comparison, a higher number of medical and spontaneous abortions were reported by women from less privileged socioeconomic classes. CONCLUSION: Iranian policymakers are concerned about the declining fertility rate and have turned to pronatalist policies. From a demographic standpoint, this seems to be a reasonable approach. However, the new population policies, particularly, the Family Protection and Young Population Law, along with creating limitations in access to reproductive health services and prenatal screening tests as well as stricter abortion law could potentially lead to an increase in various types of abortions and their associated consequences.
Keywords: Abortion, Spontaneous; lidé; socioekonomické faktory; indukovaný potrat; Írán; Female; Pregnancy; Abortion, Induced; Iran; těhotenství; samovolný potrat; potrat nezákonný; Socioeconomic Factors; ženské pohlaví; Abortion, Illegal; Humans